Eksplorasi Sekte Khawarij Dan Impresinya Terhadap Ajaran Islam - Bangkit Nugraha; Ariska Sara; Naila Nur Hikmah; Samsul Ma’arif; Izmi Nurul Azizah; Muhamad Parhan; Nisrina Fitri Ghaida (Jurnal Budi Pekerti Agama Islam, 2024)
At first, the Khawarij emerged on the scene of kalam thought from a political point of view, as they disagreed with Ali bin Abi Talib and Mu'awiyah bin Abi Sufyan's approach to resolving Muslim disputes by arbitration (tahkim). However, later kalam thought developed in a theological direction. The Khawarij argued that resolving Muslim conflicts through tahkim violated God's law and was a great sin, so the blood of those who did tahkim was halal. Their attitudes and behavior were influenced by Khawarij teachings, including the issue of the position of caliph, mu'amalah among non-Khawarij Muslims, and zuhud and worship. In addition to beliefs such as understanding the nature of faith and tawhid, Allah's promises and threats, the Qur'an is a creature, and takwil and qiyas are also the basis of their actions. Historically, Khawarij split into various sects such as Azariqah, Shufriyah and Ibadhiyah. This paper will discuss the historical issues of the emergence of Khawarij, teachings and sects in Khawarij.